The impact of sociocultural transformations on the ancient Arab poetic art - Diaf, Mohamed (Journal of Human Sciences, 2022)
This article aims at examining a methodological critical approach by means of studying the impact the sociocultural changes on the formation of artistic work. Art is a reflection of the social phenomenon, the political events and the economic conditions which places the act in a defined time and environment.